Management of complex and redo cases of pelvic fracture urethral injuries - Sanjay B. Kulkarni; Sandesh Surana; Devang J. Desai; Hazem Orabi; Subramanian Iyer; Jyotsna Kulkarni; Ajit Dumawat; Pankaj M. Joshi (Asian Journal of Urology)
Objectives: Pelvic fracture urethral injuries (PFUI) result from traumatic disruption of the urethra. A significant proportion of cases are complex rendering their management challenging. We described management strategies for eight different complex PFUI scenarios. Methods: Our centre is a tertiary referral centre for complex PFUI cases. We maintain a prospective database (1995–2016), which we retrospectively analysed. All patients with PFUI managed at our institute were included. Results: Over two decades 1062 cases of PFUI were managed at our institute (521 primary and 541 redo cases). Most redo cases were referred to us from other centres. Redo cases had up to five prior attempts at urethroplasty. We managed complex cases, which included bulbar ischemia, young boys and girls with PFUI, PFUI with double block, concomitant PFUI and iatrogenic anterior urethral strictures. Bulbar ischemia merits substitution urethroplasty, most commonly, using pedicled preputial tube. PFUI in young girls is usually associated with urethrovaginal fistula. Young boys with PFUI commonly have a long gap necessitating trans-abdominal approach. Our success rate with individualised management is 85.60% in primary cases, 79.13% in redo cases and 82.40% in cases of bulbar ischemia. Conclusion: The definition of complex PFUI is ever expanding. The best chance of success is at the first attempt. Anastomotic urethroplasty for PFUI should be performed in experienced hands at high volume centres. Keywords: Urethral reconstruction, Pelvic fracture urethral distraction defects, Pelvic fracture urethral injuries, Bulbar necrosis, Long gap, Bladder neck injury, Rectourethral fistula